Penggunaan Media Cerita Gambar untuk Meningkatkan Keterampilan Pemahaman Membaca Siswa Kelas IV di SDN Cengkal Sewu 01 - Amelia Dea Puspita Az’zahra; Siti Muflikah; Zulfa Khusnul Aqna; Diana Ermawati (FKIP, Universitas Palangka Raya, 2024)
This research is motivated by low turnover and the consequences of students' perceptual abilities, this is indicated by the large number of students who are still in KKM which is not fully established. Normal education which reduces creativity and learning dynamics is one of the factors causing the low spirit of honesty. By using picture story media, the purpose of this study is to enhance students' developing experiences. Research on the development of homeroom teachers (vehicles) with a rotary model is an exploratory technique used. This study involved 24 grade IV students at SDN Cengkalsewu 01, Cengkalsewu Region, Pati Regency. Through tests and perceptions, information is collected. Data were examined using various abstract and quantitative approaches. The audit results show that picture story media is increasingly being used in creating experiences. This can be seen from the level of student movement which includes concentration when the instructor understands the material, effectively solves urgent problems, and considers answering the instructor's questions. There is an increase in the ability to read difficulties in each cycle. With an average score of 67.08, 8 students (33.33 percent) in cycle I reached a high level. In cycle II there were 18 students (75.00%) who won with an average score of 77.91. Using picture story media can only broaden the tendencies of ordinary students and creative minds, as revealed by previous investigations.